Analysis of the Performance of the Apparatus of the Protocol and Communication Section of the Regional Secretariat Leaders in Supporting the Activities of the Mayor of Bandung - Panji Anugerah Januar Mi'raz; Muhadam Labolo; Tjahyo Suprayogo (INFOKUM, 2025)
This research is motivated by the lack of performance of human resources in the Protocol and Leadership Communication Section at the Bandung City Regional Secretariat. The purpose of the study was to analyze and determine the performance of human resources in the Protocol and Leadership Communication Section at the Bandung City Regional Secretariat. Then using a descriptive qualitative method. The data sources used are primary data and secondary data. Data collection techniques through observation, interviews and documentation. Data analysis methods with data reduction, data presentation and drawing conclusions. The results of the study showed that the Analysis of the Performance of the Protocol and Leadership Communication Section of the Regional Secretariat in Supporting the Activities of the Mayor of Bandung. The productivity indicator has been implemented but is still not optimal.apparatus resources of the Protocol and Communication Section of the Bandung City Regional Secretariat. The indicators of responsibility and accountability have been implemented quite well. The indicators of responsiveness based on the results of the study are still not optimal. Then, the indicators of service qualityapparatus resources of the Protocol and Communication Section of the Bandung City Regional Secretariathas been implemented quite well. Inhibiting FactorsProtocol and Communication Section of the Regional Secretariat of Bandung Cityin improving the performance of human resources, namely the limited number of human resources and the lack of coordination between agencies. Then efforts are made to overcome inhibiting factorsProtocol and Communication Section of the Regional Secretariat of Bandung Cityin improving performance apparatus resources, namely increasing apparatus resources and increasing coordination between agencies